Initial Development and Validation of a Transition Readiness Scale for Adolescents with Inflammatory Bowel Disease. (18th June 2019) - Hammerman, Oded; Bayatra, Areej; Turner, Dan; Levine, Arie; Shamir, Raanan; Assa, Amit; Wilschanski, Michael; Bachner, Yaacov G.; Israeli, Eran
Abstract : Background and Aims . To date, there are no validated measures in IBD to assess the level of preparedness for transition into adult health care. The purpose of this study was to develop and assess the reliability and validity of a "Transition Readiness" (TR) measure for adolescents with IBD, as well as to evaluate the level of TR synchronicity between adolescents themselves, their parents, and their pediatric gastroenterologists. Methods . A self-assessment tool was created to evaluate TR. Items were reviewed for face validation by IBD experts, and an exploratory factor analysis was performed which yielded 3 distinct domains. The study cohort included adolescents aged 12-21 yrs, their parents, and their physicians in pediatric IBD centers. Correlations between patient/parent/physician TR between each of the domains and the overall TR score to age were assessed. Results . 63 subjects (average age 16.6 yrs/79% Crohn's disease/44% male) participated in this study. There was a significant correlation between the scoring of adolescents and parents on all three domains. The correlation between adolescents and physicians, as well as between parents and physicians, was only consistent for self-efficacy. Self-efficacy significantly correlated with age, while the correlations between perceived knowledge and perception of medical care with age were not significant. Conclusion . Validation of a novel TR measurement for adolescents with IBD demonstrated a good correlation between patients and parents. Out of the three proposed constructs, perceived self-efficacy is the most salient measure.